2018
DOI: 10.1016/j.trc.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Driving behaviour at motorway ramps and weaving segments based on empirical trajectory data

Abstract: In the vicinity of ramps, drivers make route choices, change lanes and in most cases also adjust their speeds. This can trigger anticipatory behaviour by the surrounding vehicles, which are also reflected in lane changes and/or changes in speed. This phenomenon is called turbulence and is widely recognised by the scientific literature and various design guidelines. However the knowledge about the characteristics of turbulence is limited. This study investigates the microscopic characteristics of driving behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 37 publications
6
45
0
Order By: Relevance
“…This is in line with another study highlighting that expressway drivers would more often cooperate with merging vehicles through lane-changing than through decelerating (Kondyli & Elefteriadou, 2012). Beinum, Farah, Wegman, & Hoogendoorn, (2018) investigated the microscopic characteristics of driving behavior around on-ramps, off-ramps and weaving segments in the Netherlands. They found that abrupt lane changes create turbulence in the traffic flow .…”
Section: Introductionsupporting
confidence: 79%
“…This is in line with another study highlighting that expressway drivers would more often cooperate with merging vehicles through lane-changing than through decelerating (Kondyli & Elefteriadou, 2012). Beinum, Farah, Wegman, & Hoogendoorn, (2018) investigated the microscopic characteristics of driving behavior around on-ramps, off-ramps and weaving segments in the Netherlands. They found that abrupt lane changes create turbulence in the traffic flow .…”
Section: Introductionsupporting
confidence: 79%
“…However, the potential impacts of platoon clustering strategies on non-equipped vehicles (i.e., HVs) have been seldom studied. Empirical trajectory data revealed that lane change caused by merging and diverging vehicle creates most motorway turbulence (van Beinum et al, 2018). Therefore, CACC may influence the characteristics of the HV flow when a local coordination strategy is employed.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the in-vehicle navigation information had significant positive effects on lane-changing behaviors under medium to high-density conditions but less effective under light density conditions. The study of van Beinum, Farah, Wegman, and Hoogendoorn (2018) showed that lane changes caused by merging and diverging vehicles create most turbulencean increase in the amount of traffic leads to a higher level of turbulence, and larger available space for merging and diverging results in the lower level of turbulence. Tilg, Yang, and Menendez (2018) further considered the automated vehicle (AV) and proposed a multiclass hybrid model and a simulation-based optimization framework to study how AV technology can improve the stability of the operation and increase the capacity of weaving sections.…”
Section: Introductionmentioning
confidence: 99%